Republic of Kosovo : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper on Kosovo discusses various challenges and opportunities in the public infrastructure domain. Given the very low initial stocks, largely due to the sharp depletion of capital stock during the conflicts in the 1990s, higher investment rates are needed. The resources available from international development partners, including the European Union (EU), the European Investment Bank and the European Bank for Reconstruction and Development, are a unique opportunity to leverage and accelerate the implementation of priority projects. Strengthening Kosovo's investment framework is key to achieving this objective. Kosovo faces significant public infrastructure gaps, which constrain private sector development. Scaling-up public investment will raise gross domestic product growth potential and accelerate income convergence toward the EU average level. The priority project list has helped the authorities to prioritize plans and facilitate the discussions and negotiations with donors and International Financial Institutions (IFI). However, implementation so far has been modest, despite the new investment clause of the fiscal rule exempting IFI-financed projects from the deficit ceiling.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet